Web-based handling of the administrative tasks in a master thesis - Palo, Fredrik; Raattamaa, Mattias (2004)
At the Department of Computer Science and Electrical Engineering at Luleå University of Technology, all administrative tasks of master theses are handled on paper. This is an inefficient and old-fashioned approach, with much room for improvement. Because of this, there was a desire among the department staff for a more modern system. This report describes the process of designing, developing and evaluating such a system. During this project, common practices of software development have been used. Starting as a paper prototype, our suggested solution evolved through two iterations into a system meeting most of the requirements. Limited user tests were conducted to evaluate the design of the system’s user interface. The resulting system consists of a user-authenticated web site were users perform all master thesis related tasks and a MySQL database storing all information. Important system events are logged and users are notified of waiting tasks by e-mail. One conclusions made during the project is that the core functionality should have been given more time, instead of focusing to much on functions less important for the system completeness. Also, external systems should have been examined earlier in the project to take advantage of already existing information, and thus avoiding redundant implementation of input forms. Validerat; 20101217 (root)